Extraction of cobalt(II) from aqueous hydrochloric acid solutions into alamine 336-m-xylene mixtures - SAYAR, NİHAT ALPAGU (ELSEVIER, 2006)
Extraction of Co(II) from aqueous hydrochloric acid solutions into organic Alamine 336-m-xylene systems was investigated. Extraction experiments were conducted with initial metal concentrations of 1, 3 and 6 g L-1, each at 1, 5, 8 and 10 M HCl. It was observed that the extractability of Co(II) increases with increasing acidic molarities. Alamine 336 diluted with m-xylene was found to be a suitable extractant for Co(II) for 5 to 10 M. In parallel, extractant volume-domain dynamics were investigated. A mathematical model was developed to correlate metal extractability and Alamine 336 volume content. Optimal Alamine 336 contents were estimated for single stage extraction. (c) 2006 Elsevier B.V. All rights reserved.
Keywords: Co(II) solvent extraction; alamine 336; model; CHAIN ALKYL AMINES; GROUP-VIII METALS; SOLVENT-EXTRACTION; CHLORIDE SOLUTIONS; SYNERGIC EXTRACTION; CARBOXYLIC-ACIDS; SEPARATION; NICKEL; CADMIUM; COPPER